Recent Advances in Nonlinear Dynamics and Synchronization Theory and Applications - Kyamakya, Kyandoghere; Unger, Herwig; Chedjou, Jean Chamberlain; Rulkov, Nikolai F.; Li, Zhong (Studies in Computational Intelligence, 2009)
The selected contributions of this book shed light on a series of interesting aspects related to nonlinear dynamics and synchronization with the aim of demonstrating some of their interesting applications in a series of selected disciplines. This book contains thirteenth chapters which are organized around five main parts. The first part (containing five chapters) does focus on theoretical aspects and recent trends of nonlinear dynamics and synchronization. The second part (two chapters) presents some modeling and simulation issues through concrete application examples. The third part (two chapters) is focused on the application of nonlinear dynamics and synchronization in transportation. The fourth part (two chapters) presents some applications of synchronization in security-related system concepts. The fifth part (two chapters) considers further applications areas, i.e. pattern recognition and communication engineering.